GENDER DISCRIMINATION PORTRAYED IN CAROL LYNCH WILLIAMS’ THE CHOSEN ONE - Alfarina, Shella (Annual International Conferences on Language, Literature, and Media, 2022)
Gender discrimination occurs because of the domination of beliefs and justifications instilled throughout human civilization in various forms experienced by women. This article aims to explain the kinds of gender discrimination experienced by Kyra and its impacts on her in Carol Lynch Williams’ The Chosen One (2009). This study is categorized into literary criticism and applies the theory of gender discrimination proposed by Wolf (1993) & (2002). This study found four kinds of gender discrimination: gender discrimination in marriage, gender discrimination in education, gender discrimination in religion, and gender discrimination in the domestic area. First, the impact of gender discrimination in marriage is pregnancy disorders that cause death and mental disorders, psychological disorders, and negative assumption. Second, the impact of gender discrimination in education is the loss of the right to get a position in government. Third, the impact of gender discrimination in religion is excessive fanaticism. Finally, the impact of gender discrimination in the domestic area is death.